2002
DOI: 10.1016/s0014-5793(02)02610-8
|View full text |Cite
|
Sign up to set email alerts
|

Zinc is required for structural stability of the C‐terminus of archaeal translation initiation factor aIF2β

Abstract: aIF2L L is an archaeal homolog of eukaryotic translation factor eIF2L L necessary for translation initiation and involved in recognition of the initiation codon. In the present study, we demonstrate for the first time zinc binding to the C 2^C2 zinc finger at the C-terminus of aIF2L L. Nuclear magnetic resonance backbone assignments were also determined and the secondary structural elements identified. ß 2002 Published by Elsevier Science B.V. on behalf of the Federation of European Biochemical Societies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Although this loop includes bC107 and bC110 of the C2-C2 zinc-binding motif, the tetrahedral coordination to the zinc ion is retained in the present conformation (Fig. 4A), which is consistent with the essentiality of the zinc ion in the stability of aIF2␤ (18). ZBD in the complex is packed closely to HTH, and an interdomain hydrogen bond is discernible between the conserved bT115 in ZBD and bR58 in HTH, in contrast to the uncomplexed form, which shows no obvious interaction between the domains.…”
Section: Resultssupporting
confidence: 79%
“…Although this loop includes bC107 and bC110 of the C2-C2 zinc-binding motif, the tetrahedral coordination to the zinc ion is retained in the present conformation (Fig. 4A), which is consistent with the essentiality of the zinc ion in the stability of aIF2␤ (18). ZBD in the complex is packed closely to HTH, and an interdomain hydrogen bond is discernible between the conserved bT115 in ZBD and bR58 in HTH, in contrast to the uncomplexed form, which shows no obvious interaction between the domains.…”
Section: Resultssupporting
confidence: 79%
“…The zinc‐finger domain (residues 99–135) is composed of three antiparallel β‐strands (β5, β6, and β7) encompasing residues 112–116, 120–124, and 128–130, respectively. Zinc is required for the structural stability of this domain (Gutierrez et al 2002), and is coordinated by four cysteines at positions 102, 105, 123, and 126. Helix α4, links the core domain and the zinc finger.…”
Section: Resultsmentioning
confidence: 99%
“…Helix α4, links the core domain and the zinc finger. The absence of significant chemical shift changes in the core domain upon folding of the C terminus (Cho and Hoffman 2002; Gutierrez et al 2002), the lack of NOEs between the two domains and their different RDC alignment tensors suggest that there are minimal interactions between the core domain and the zinc finger. Superposition of the core and zinc finger domains of Mj_aIF2β to Mt_aIF2β gives backbone RSMDs of 2.24 Å.…”
Section: Resultsmentioning
confidence: 99%
“…First, it is reasonable that the two proteins (ribosome-binding factor A [spot 24] and GTPbinding translation factor [spot 427]) were derepressed in the ⌬310 mutant. Several studies have indicated that zinc is required for the structural stability of translation initiation fac- (22,35). It is possible that ribosome-binding factors compete with a translation initiation factor for the resources of ribosomes (19,21).…”
Section: Discussionmentioning
confidence: 99%